Changes in trauma-potentiated startle, skin conductance, and heart rate within prolonged exposure therapy for PTSD in high and low treatment responders. (December 2019) - Maples-Keller, Jessica L.; Rauch, Sheila A.M.; Jovanovic, Tanja; Yasinski, Carly W.; Goodnight, Jessica Morgan; Sherrill, Andrew; Black, Kathryn; Michopoulos, Vasiliki; Dunlop, Boadie W.; Rothbaum, Barbara Olasov; Norrholm, Seth Davin
Highlights: Psychophysiological data are important indices for investigating treatment response. We tested startle, heart rate, and skin conductance in exposure therapy for PTSD. Trauma-potentiated startle demonstrated differences in high and low responders. Abstract: While exposure-based psychotherapy is recommended as a first-line treatment for posttraumatic stress disorder (PTSD) given strong evidence for its effectiveness, some patients fail to receive full benefit. Psychophysiological data may be important complementary indices for investigating variability in treatment response and changes over the course of treatment. The focus of the present investigation was to examine change in psychophysiological indices pre- to post-treatment and to investigate if changes differed for high versus low PTSD treatment responders. Participants included veterans with primary PTSD diagnoses who received a two-week intensive prolonged exposure (PE) treatment. Psychophysiological assessment included trauma-potentiated startle, heart rate, and skin conductance recordings during presentation of three standard virtual reality (VR)-based, trauma-relevant scenes presented through a head mounted display. Results indicate that 48.6% were classified as high treatment responders (≥50% reduction in PCL-5 from baseline). Trauma-potentiated startle was observed in all patients at pre-treatment, F = 13.58, p < .001, in that startle magnitude was increased during VR stimuli relative to baseline regardless of responder status. However, in high treatment responders, there was an interaction of VR with time, F = 14.10, p = .001; VR scenes did not potentiate startle post-treatment. Specifically, high treatment responders were less reactive to trauma stimuli following PE treatment. There was no effect of time in the low responder group. Heart rate reactivity data revealed a significant main effect of treatment, F = 45.7, p = .035, but no significant interaction with responder status. Skin conductance reactivity did not significantly change from pre to post-treatment. These results suggest that trauma-potentiated startle may represent an objective marker of fear- and anxiety-related symptom reduction that is sensitive to both traditional outpatient as well as intensive treatment approaches.